TRENDS IN CONSUMPTION OF MILK AND DAIRY PRODUCTS IN SLOVAKIA AFTER EU ACCESSION - Dušan Dobák; Zdenka Kádeková; Lubica Kubicova (Polityki Europejskie, Finanse i Marketing)
In the paper are evaluated changes and development in consumption of milk and dairy products in recent years from accession of Slovakia to the European Union in 2004. Consumption of milk and dairy products in Slovakia lags far behind countries of the former EU-15. Consumption of these products in the value milk free butter was 158.6 kg in 2012. Compared with ODP, dairy consumption 220 kg in 2012 was of 61.4 kg less and considering its importance is nutritionally unfavorable. Particularly unfavorable was consumption of drinking milk, which ensured recommended amount of food only at 60%. Only the consumption of cheese and curd was at the level of given recommended amount 10.1 kg.